Estratégias lúdicas inseridas na experência do usuário: Duolingo e sua forma de aproximação - Cabral, Ana Carolina Simões de Freitas (2018)
Not everyone has the ease and pleasure to learn new languages. However, learning languages is increasingly important. With regard to entry into the labor market, for example, 91% of executives from different countries interviewed in the Global English Corporation survey believe that English is the main language of business. In the search for a solution to this issue, combining learning, translation and gamification, the Duolingo application was able to facilitate this task for users of the platform, who got involved and learned languages with the help of it. However, although widely used and well-evaluated in digital stores, under an academic view, many articles criticize its methodology (SANTANA, 2016; MOTA et al., 2016; DUARTE et al., 2016; BOGDAN, 2016; VALADARES et al., 2016; Gavarri, 2016), believing that it is inappropriate for this teaching. But if the methodology used is said to be ineffective, what corroborated for the application to reach so many users? This research aimed to evaluate heuristically (NIELSEN AND MOLICH, 1990; DESURVIRE et al., 2004; MALONE, 1980; PINELLI et al, 2008) the design of Duolingo interface and the way you interact directly with your users by playful aspects, in order to understand the relevance of these in the popularization of the application. In this way, we evaluated the role of user experience in the use of the application, the involvement with the learning offered there and the return to the use of the interface. It was inferred from the obtained results that, in the search for applications that can aid in the learning of foreign languages, it is not only the educational aspects and the contents presented that govern the choice of the users, they also look for easily understandable interfaces and personally satisfying experiences, apt to add intrinsic motivation to learning